MESSAGE PACKAGING THROUGH DATA-DRIVEN STORYTELLING IN FOOD RESCUE EFFORTS (INSTAGRAM DESCRIPTIVE STUDY @FOODBANKBANDUNG BY FOOD BANK BANDUNG) - Kartika, Ghinaa Azalia; Bakti, Iriana; Budiana, Heru Ryanto (Journal of Social Science, 2024)
General Background: Food waste is a pressing global issue, with significant environmental and social implications. Effective communication strategies are essential for raising awareness and driving action in food rescue initiatives. Specific Background: Food Bank Bandung utilizes data-driven storytelling on Instagram to address food waste, employing techniques such as narrative communication, data explanation, and structured content presentation. While these methods enhance audience engagement by merging emotional narratives with empirical data, challenges remain in ensuring data transparency and fostering long-term audience engagement. Knowledge Gap: Despite the apparent effectiveness of data-driven storytelling, limited research exists on its application in the context of food rescue initiatives, particularly regarding audience comprehension and the consistency of data updates. Aims: This study aims to provide an in-depth evaluation of the strategies employed by Food Bank Bandung in their data-driven storytelling efforts on Instagram, focusing on how these strategies shape impactful narratives for local audiences. Results: Through qualitative descriptive methods, including in-depth interviews with operational teams and content analysis of Instagram publications, the study reveals that Food Bank Bandung effectively enhances public awareness and trust by transparently presenting operational data on food rescue activities. However, challenges such as inconsistent data updates and audience misunderstanding of data remain. Novelty: This research contributes to the field of communication studies by elucidating the specific strategies used in data-driven storytelling for food rescue, highlighting the intersection of narrative engagement and data transparency. Implications: The findings underscore the need for improved data presentation techniques and regular updates to enhance audience comprehension, ultimately advancing the effectiveness of food rescue campaigns in urban settings.